2020
DOI: 10.1136/jmedgenet-2020-106844
|View full text |Cite
|
Sign up to set email alerts
|

Otitis media susceptibility and shifts in the head and neck microbiome due to SPINK5 variants

Abstract: BackgroundOtitis media (OM) susceptibility has significant heritability; however, the role of rare variants in OM is mostly unknown. Our goal is to identify novel rare variants that confer OM susceptibility.MethodsWe performed exome and Sanger sequencing of >1000 DNA samples from 551 multiethnic families with OM and unrelated individuals, RNA-sequencing and microbiome sequencing and analyses of swabs from the outer ear, middle ear, nasopharynx and oral cavity. We also examined protein localisation and gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Although the novel rare variants we identified might have potential effects on protein structure based on molecular modeling, PLG expression is very low or absent in normal or diseased middle ear tissues in both mouse and human. Our previous studies support a common mechanism by which the OM susceptibility variant affects expression of the encoded protein and other genes downstream, which in turn shifts the middle ear microbiome by changing the overall biodiversity or relative abundance of specific pathogens or commensal taxa 16,21,46,47 . The mostly negative results of our multiple studies showed that this disease mechanism does not apply to PLG variants in relation to OM susceptibility in humans.…”
Section: Discussionsupporting
confidence: 67%
“…Although the novel rare variants we identified might have potential effects on protein structure based on molecular modeling, PLG expression is very low or absent in normal or diseased middle ear tissues in both mouse and human. Our previous studies support a common mechanism by which the OM susceptibility variant affects expression of the encoded protein and other genes downstream, which in turn shifts the middle ear microbiome by changing the overall biodiversity or relative abundance of specific pathogens or commensal taxa 16,21,46,47 . The mostly negative results of our multiple studies showed that this disease mechanism does not apply to PLG variants in relation to OM susceptibility in humans.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, no differences in beta-diversity were observed in association with biological sex (p=0.20) or cephalosporin use (p=0.37). Only a few patients were positive for [a] use of local steroid as a component of antibiotic otic drops and [b] for FUT2 or SPINK5 variants ( Table 1 ), which we have previously shown to be determinants of ME microbiota ( Santos-Cortez et al., 2018 ; Frank et al., 2020 ; Elling et al., 2022 ); consequently, steroid use, FUT2 genotype, and SPINK5 genotype were excluded from all analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial 16S rRNA genes were amplified from DNA samples using primers specific for the V1V2 region (27FYM 5’-AGAGTTTGATYMTGGCTCAG and 338R 5’-TGCTGCCTCCCGTAGGAGT), as previously described ( Santos-Cortez et al., 2018 ; Bootpetch et al., 2020 ; Frank et al., 2020 ). All work was performed in either a biosafety level 2 hood or a HEPA-filtered PCR hood following 15 minutes of ultraviolet irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…Nasopharyngeal microbial composition differs between OM-prone and nonprone children [ 17 , 29 ]. Future studies could examine association between NREP and microbiomes of CSOM-prone Aboriginal children, complementing knowledge of rare variants at A2ML1 and SPINK5 and middle ear microbiomes in Filipino OM patients [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%